The impact of information technology on tax evasion (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims at shedding light on the impact of information technology in reducing tax evasion in the General Authority for Taxation. In order to achieve this, the research relied on the analysis of its variables as a main tool for collecting data and information. The results showed that there is a positive and positive effect of information technology on tax evasion. The impact of information technology on increasing tax revenues and reducing the phenomenon of tax evasion In the performance of the research sample, the research sought to highlight the importance of tax information technology through its data and information to the tax administration for the purpose of completing the process Taxpayers for persons subject to income tax are natural persons or legal persons (companies), as information technology contributes to the provision of accurate and reliable information in a timely manner.